Gravity-driven membrane filtration with compact second-life modules daily backwashed: An alternative to conventional ultrafiltration for centralized facilities - Deborah Stoffel; Nicolas Derlon; Jacqueline Traber; Christian Staaks; Martin Heijnen; Eberhard Morgenroth; Céline Jacquin (Water Research X, 2023)
Gravity-driven membrane (GDM) filtration is a strategic alternative to conventional ultrafiltration (UF) for the resilient production of drinking water via ultrafiltration when resources become scarce, given the low dependency on energy and chemicals, and longer membrane lifetime. Implementation at large scale requires the use of compact and low-cost membrane modules with high biopolymer removal capacity. We therefore evaluated (1) to what extent stable flux can be obtained with compact membrane modules, i.e., inside-out hollow fiber membranes, and frequent gravity-driven backwash, (2) whether we can reduce membrane expenses by effectively utilizing second-life UF modules, i.e., modules that have been discarded by treatment plant operators because they are no longer under warranty, (3) if biopolymer removal could be maintained when applying a frequent backwash and with second-life modules and (4) which GDM filtration scenarios are economically viable compared to conventional UF, when considering the influence of new or second-life modules, membrane lifetime, stable flux value and energy pricing. Our findings showed that it was possible to maintain stable fluxes around 10 L/m2/h with both new and second-life modules for 142 days, but a daily gravity-driven backwash was necessary and sufficient to compensate the continuous flux drop observed with compact modules. In addition, the backwash did not affect the biopolymer removal. Costs calculations revealed two significant findings: (1) using second-life modules made GDM filtration membrane investment less expensive than conventional UF, despite the higher module requirements for GDM filtration and (2) overall costs of GDM filtration with a gravity-driven backwash were unaffected by energy prices rise, while conventional UF costs rose significantly. The later increased the number of economically viable GDM filtration scenarios, including scenarios with new modules. In summary, we proposed an approach that could make GDM filtration in centralized facilities feasible and increase the range of UF operating conditions to better adapt to increasing environmental and societal constraints.